2021
DOI: 10.3390/su131910580
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Mobile Apps to the Improvement of Walking/Cycling Behavior Considering the Impacts of COVID-19 Pandemic

Abstract: More than one hundred and fifty cities around the world have expanded their emergency cycling and walking infrastructures to increase their resilience in the face of the COVID-19 pandemic. In addition, the role of mobile apps is prominent in respect to developing a smart city during this pandemic, which raises the questions of how mobile apps contribute to the improvement of walking/cycling behavior and how such a relationship is influenced by the situation imposed by COVID-19. The role of mobile apps in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 127 publications
0
8
0
Order By: Relevance
“…The presence of other people is one of the features (found in this research) that contribute to reducing the sense of insecurity [75]. The presence of people helps to lessen the feeling of insecurity by acting as natural monitoring along the pathways [76]. Greater tranquility is also related to the lower presence of others as well.…”
Section: The Associations Between Design Characteristics and Walking ...mentioning
confidence: 82%
“…The presence of other people is one of the features (found in this research) that contribute to reducing the sense of insecurity [75]. The presence of people helps to lessen the feeling of insecurity by acting as natural monitoring along the pathways [76]. Greater tranquility is also related to the lower presence of others as well.…”
Section: The Associations Between Design Characteristics and Walking ...mentioning
confidence: 82%
“…However, the most commonly considered indicators are bicycle infrastructure, greenery along bicycle paths, slopes, vehicular traffic flow/volume, street lights, bicycle path connectivity, and traffic speed. These indicators are related to the sense of comfort and safety along the bicycle pathways, which, when offered, results in a preference of people to choose bicycles over other modes of transport [75]. Past research shows that other indicators, along with cycle infrastructure, such as pavement conditions, road markings, traffic control devices, and crosswalks, play a significant role in getting people to ride bikes [7,76].…”
Section: Discussionmentioning
confidence: 99%
“…According to ecological models, a person's walking behavior is influenced b complex relationship between environmental (physical/social) and individual charac istics (Krogstad et al 2015;Rind et al 2015;Van Cauwenberg et al 2014). In this reg previous studies have demonstrated the impact of several personal as well as cio-demographic, social, and built environment factors in improvement of walking havior (Copperman and Bhat 2007;Inoue et al 2010;Mesters et al 2014;Paydar Kamani Fard 2016;Paydar et al 2017;Paydar and Kamani Fard 2021a;Van Cauwenb et al 2012;Yun 2019). However, the previous studies on walking behavior mostly cused on the contribution of built environment to walking behavior, whereas the ro socio-demographic as well as social factors in improvement of walking behavior has b less studied.…”
Section: Introductionmentioning
confidence: 99%